2017
DOI: 10.1088/1748-3190/aa7c89
|View full text |Cite
|
Sign up to set email alerts
|

Tunable multimodal adhesion of 3D, nanocrystalline CoFe2O4pollen replicas

Abstract: 3D replicas of sunflower pollen microparticles, comprised of a multicomponent magnetic spinel ferrite (CoFeO) with tailorable adhesive properties, have been synthesized for the first time via a conformal layer-by-layer (LbL) surface sol-gel (SSG) deposition process followed by organic pyrolysis and oxide compound formation at a peak temperature of 600 °C-900 °C. These high-fidelity ferrite pollen replicas exhibited multimodal (van der Waals, vdW, and magnetic) adhesion that could be tuned via control of the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Pollen particles represent an ideal source of natural microparticles for use in developing microparticle‐stabilized Pickering emulsion systems. Pollens exhibit numerous desirable properties for functional emulsion applications, such as particle monodispersity, physicochemical robustness, amphiphilicity, biocompatibility, and diverse surface chemistry options for functionalization and compound binding . In general, there is growing interest in utilizing pollen microparticles for a wide range of applications, such as the extraction of pollen shells for microencapsulation and drug delivery applications .…”
Section: Introductionmentioning
confidence: 99%
“…Pollen particles represent an ideal source of natural microparticles for use in developing microparticle‐stabilized Pickering emulsion systems. Pollens exhibit numerous desirable properties for functional emulsion applications, such as particle monodispersity, physicochemical robustness, amphiphilicity, biocompatibility, and diverse surface chemistry options for functionalization and compound binding . In general, there is growing interest in utilizing pollen microparticles for a wide range of applications, such as the extraction of pollen shells for microencapsulation and drug delivery applications .…”
Section: Introductionmentioning
confidence: 99%
“…Uddin et al [4,5] have demonstrated the oral delivery of vaccines to mice via ragweed pollen and the potential for pollen to be used for controlled release of pharmaceuticals has been reviewed [6]. Moreover, pollen have been used as templates for fabricating metal-oxide magnetic replicas [7,8], magnetic-core particles [9] and metallized shells [10] with unique combinations of multimodal adhesion and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Biologically derived particules including pollen, virus, and bacteria have attracted interest as templates for synthetic inorganic mimics that also possess properties such as magnetic forces and unique spectroscopic signatures [9][10][11][12][13]. Due to their complex biologically derived morphology, these mimics may provide unique function as fillers.…”
Section: Introductionmentioning
confidence: 99%